Gut Microbiota and Serum Metabolome in Elite Cross-Country Skiers: A Controlled Study - Hintikka Jukka E.; Munukka Eveliina; Valtonen Maarit; Luoto Raakel; Ihalainen Johanna K.; Kallonen Teemu; Waris Matti; Heinonen Olli J.; Ruuskanen Olli; Pekkala Satu (MDPI, 2022)
Exercise has been shown to affect gut the microbiome and metabolic health, with athletes typically displaying a higher microbial diversity. However, research on the gut microbiota and systemic metabolism in elite athletes remains scarce. In this study, we compared the gut microbiota profiles and serum metabolome of national team cross-country skiers at the end of an exhausting training and competitive season to those of normally physically-active controls. The gut microbiota were analyzed using 16S rRNA amplicon sequencing. Serum metabolites were analyzed using nuclear magnetic resonance. Phylogenetic diversity and the abundance of several mucin-degrading gut microbial taxa, including Akkermansia, were lower in the athletes. The athletes had a healthier serum lipid profile than the controls, which was only partly explained by body mass index. Butyricicoccus associated positively with HDL cholesterol, HDL2 cholesterol and HDL particle size. The Ruminococcus torques group was less abundant in the athlete group and positively associated with total cholesterol and VLDL and LDL particles. We found the healthier lipid profile of elite athletes to co-occur with known health-beneficial gut microbes. Further studies should elucidate these links and whether athletes are prone to mucin depletion related microbial changes during the competitive season.